Analysis of the Application of PSAP No. 07 Concerning Accounting for Fixed Assets at the Settlement Infrastructure Center for the North Sulawesi Region, Directorate General of Cipta Karya, Ministry of PUPR - Gabriela Nikita Mose; Jenny Morasa; Wulan Kindangen (Jurnal Ekonomi dan Bisnis Digital, 2023)
The state was built by the community so that people's lives obtain peace, comfort, prosperity, justice and progress in outer and inner life. The achievement of state goals, one of them, depends on the government as the organizer of the state. Fixed asset accounting is a form of managing state property. The management of state/regional property is regulated in government regulation no. 27 of 2014. The purpose of this study is to determine the suitability of the Application of Statement of Government Accounting Standards (PSAP) No. 07 concerning the accounting for fixed assets at the North Sulawesi Regional Settlement Infrastructure Center, Directorate General of Cipta Karya, Ministry of PUPR. The analytical method uses a qualitative descriptive analysis method. From this study it was found that in analyzing the application of Statement of Governmental Accounting Standards (PSAP) No. 07 regarding the accounting for fixed assets at the North Sulawesi Settlement Infrastructure Center in the classification, valuation, expenditure after acquisition, depreciation, retirement and disposal and disclosure of fixed assets in accordance with Statement of Government Accounting Standards (PSAP) no. 07.